Percepções sobre a natureza e a dinâmica de atuação do profissional de contabilidade no estado do Ceará: estudo exploratório - Silva, Robinson Passos de Castro e (2008)
The demands of the accounting services' users have changed together with the modern world, with their expectations regarding the services given by the accounting professionals suffering significant transformations. This study was aimed to identify the predominant perceptions between the users of accounting services and between the accounting professionals themselves regarding the nature and the dynamics of their job. In its initial stage it was based on a literature research and was then complemented with an e-mail data performed in the State of Ceará, through a qualitative approach. The research found that 68.2% of the accountants believe the society has a negative image of them. The results show that bureaucratic tasks are very frequent according to the sample. In sight of the found results, the conclusion is that the accounting profession is associated to bureaucratic and fiscal tasks. The improvement of their public image is directly related to their participation in the company's decision-making core.